Global Well-Posedness and Exponential Stability Results for Bresse-Timoshenko Type Systems of Second Sound with Distributed Delay Term - Yazid, Fares; Chougui, Nadhir; Ouchenane, Djamel; Djeradi, Fatima Siham (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we consider a Bresse-Timoshenko type system of second sound with distributed delay term. Under suitable assumptions, we establish the global well-posedness of the initial and boundary value problem by using the Faedo-Galerkin approximations and some energy estimates. By using the energy method, we show exponential stability results for the system with distributed term delay acting in angular rotation, respectively. This extends earlier results in the literature.